2019
DOI: 10.2460/javma.255.9.1035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of concurrent analysis of cerebrospinal fluid samples collected from the cerebellomedullary cistern and lumbar subarachnoid space for the diagnosis of steroid-responsive meningitis arteritis in dogs

Abstract: Objective: To describe the clinical characteristics and outcomes in a population of dogs with negative-pressure pulmonary edema (NPPE) and to identify the main causes of the disease. To evaluate any associations with morbidity and mortality.Design: Retrospective study.Setting: Three university teaching hospitals and two private referral centers.Animals: Thirty-five client-owned dogs presented with NPPE. Interventions: NoneMeasurements and Main Results: Data collected included patient characteristics, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…24 The differential cell count of the samples with low TNCC would still have been diagnostic of SRMA in six of eight cases, based on the presence of more than 40% of neutrophils. 19,24 Traditionally, when CMC and LSS puncture sites have been compared, a higher number of TNCC in samples from the CMC and higher level of TP concentration in samples from the LSS have been found. 25 The CSF sampling is usually performed caudally to the suspected site of the lesion in the CNS.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…24 The differential cell count of the samples with low TNCC would still have been diagnostic of SRMA in six of eight cases, based on the presence of more than 40% of neutrophils. 19,24 Traditionally, when CMC and LSS puncture sites have been compared, a higher number of TNCC in samples from the CMC and higher level of TP concentration in samples from the LSS have been found. 25 The CSF sampling is usually performed caudally to the suspected site of the lesion in the CNS.…”
Section: Discussionmentioning
confidence: 89%
“…A discrepancy on the clinicopathological conclusion between the two samples was observed in one case, where only the CMC sample was diagnostic of SRMA. Recent studies have highlighted the potential clinical benefit of collecting both CMC and LSS CSF samples 24–26 . More specifically, Carletti et al 24 studied a population of 111 dogs diagnosed with SRMA with paired CSF samples (CMC and LSS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not unusual. Carletti et al 12 reported that in 18% of dogs diagnosed with SRMA had a normal or only a mildly elevated total nucleated cell count (< 10), when sampling one location only. However, when sampling the second location, all dogs were showed a clear CSF inflammation compatible with SRMA, as it was the case in this Beagle.…”
Section:  Of mentioning
confidence: 99%